EFFECT OF HOMEOPATHIC LECITHIN IN HYPERLIPIDAEMIA: AN OPEN-LABEL INTERVENTIONAL STUDY - ZANKHANA DESAI; KETAN SHAH (The Bioscan, 2025)
This open-label, single-arm clinical study investigated the effect of Lecithin homeopathic medicine on hyperlipidemia. Lecithin, a homeopathic medicine commonly used to address nutritional disorders, has also been suggested in the literature for the treatment of hyperlipidemia. Following screening, participants were recruited from outpatient department of homoeopathic medical college. They received Lecithin homoeopathic medicine in 6x potency, four pills taken orally per day for 6 weeks. Lipid profile was assessed pre and post intervention to evaluate primary outcome. A significant (p-values < 0.05) decrease in the mean value of high-density lipoprotein and an increase in low density lipoprotein and non-HDL were found in the preliminary analysis of 32 subjects. On the other hand, non-significant variations in mean value of triglyceride, VLDL, and total cholesterol were noted. Fisher's exact test, which measures the proportion change of participants in various lipid subcategories following intervention, showed no significant changes for HDL and Non-HDL. There were notable shifts in the percentage of participants in the TC and LDL subcategories of risk levels. Significantly, a shift in the percentage of participants to a lower risk category was noted for TG. Observed effects of Lecithin (6x) on lipid profiles were heterogeneous and inconclusive. However, the observed results suggest a possible role for Lecithin homeopathic medicine in modulating cholesterol metabolism through ACAT regulation, warranting further investigation.